1983
DOI: 10.1002/esp.3290080504
|View full text |Cite
|
Sign up to set email alerts
|

Flandrian relative sea level changes in the Ythan Valley, Northeast Scotland

Abstract: Relict Flandrian estuarine deposits in the Ythan valley are confined to an area in the lower valley around the present estuary. They rest upon a discontinuous layer of peat over an irregular surface of sand and gravel, and consist for the most part of a grey silty clay, or carse deposit, which forms terraces or small areas of carseland. At the seaward end ofthe estuary the grey silty clay contains a layer of grey, micaceous, silty fine sand, which tapers into the basal peat, whilst in places the surface of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 8 publications
1
33
0
Order By: Relevance
“…Following many studies of Holocene tsunami deposits (e.g., Smith et al, 1983;Minoura and Nakata, 1994;Nanayama et al, 2003;Witter et al, 2009;Chagué-Goff et al, 2012;Sawai et al, 2012), we explored the Tsunami Ramp (site T) and Drained Lake (site D) sites for potential tsunami deposits (potential deposits consist of probable and possible deposits, as discussed in the following) with handheld gouge (25 mm diameter) and Russian (50 mm diameter) corers (methods reviewed by Nelson, 2015;Fig. 3).…”
Section: Identifying Tsunami Depositsmentioning
confidence: 99%
“…Following many studies of Holocene tsunami deposits (e.g., Smith et al, 1983;Minoura and Nakata, 1994;Nanayama et al, 2003;Witter et al, 2009;Chagué-Goff et al, 2012;Sawai et al, 2012), we explored the Tsunami Ramp (site T) and Drained Lake (site D) sites for potential tsunami deposits (potential deposits consist of probable and possible deposits, as discussed in the following) with handheld gouge (25 mm diameter) and Russian (50 mm diameter) corers (methods reviewed by Nelson, 2015;Fig. 3).…”
Section: Identifying Tsunami Depositsmentioning
confidence: 99%
“…Smith et al, 1982;1983;Shennan et al, 1993;1994;1995). At present very little published information on Holocene relative sea-level changes exists for much of northern and northwest Scotland, towards the periphery of the area of isostatic uplift.…”
Section: Introductionmentioning
confidence: 97%
“…Table 5 lists both radiocarbon and calibrated dates with their altitude ranges. The table does not include the two dates used by Smith et al (1983) which are now considered in error: one from the Ythan (site 5 here), now believed to refer to a later transgression (Smith et al 2000) and one from the Montrose Basin (index point 69, site 14) believed to be in error following the observations of Shennan et al (1983). The regressive contact dates for the culmination are compared with distance along the minor axis of the Main Postglacial Shoreline quadratic trend surface ellipse, as for the rate of rise data, and are plotted in Fig.…”
Section: Culmination Of the Mid-holocene Risementioning
confidence: 99%
“…Morrison et al (1981) reasoned that radiocarbon dates from conformable contacts below and above the 'wedge' as close to the inland limit as possible, but where the minerogenic layer was at least 30 cm thick to avoid contamination of the transgressive contact date, would closely bracket the culmination and by implication date the Main Postglacial Shoreline, and Smith et al (1983) examined such dates as were then available across a range of Main Postglacial Shoreline altitudes, maintaining that the event was time-transgressive, a circumstance to be expected in glacio-isostatically affected areas, following Wright (1934). However, Haggart (1988b) doubted that diachroneity had been proven and recently it has been shown that two of the regressive contact dates used by Smith et al (1983) may be in error (Smith et al 2000).…”
Section: Culmination Of the Mid-holocene Risementioning
confidence: 99%
See 1 more Smart Citation